A Neurocognitive Approach to Early Reading Intervention for Elementary School Children with Dyslexia - Yulian Purnama; Pong Krit; Ton Kiat (Research Psychologie, Orientation et Conseil, 2025)
Early reading difficulties, particularly dyslexia, pose significant challenges for elementary school children, affecting academic achievement and long-term literacy development. Neurocognitive research suggests that deficits in phonological processing, working memory, and rapid automatized naming are core contributors to reading impairments. Understanding these underlying cognitive mechanisms is crucial for designing effective early reading interventions that target both skill acquisition and brain-based processing. This study aims to investigate the efficacy of a neurocognitive-based early reading intervention for children with dyslexia, focusing on improvements in reading fluency, decoding accuracy, and phonological awareness. A quasi-experimental design was employed with 60 elementary school participants diagnosed with dyslexia, divided into intervention and control groups. Standardized neurocognitive assessments and reading tests were administered pre- and post-intervention. Results indicated that children receiving the neurocognitive intervention demonstrated significant gains in decoding accuracy, reading fluency, and phonological awareness compared to the control group. The study concludes that interventions informed by neurocognitive principles can effectively enhance reading outcomes for children with dyslexia, providing both practical and theoretical insights into tailored literacy instruction.